2015
DOI: 10.1136/gutjnl-2014-308735
|View full text |Cite
|
Sign up to set email alerts
|

The Thr300Ala variant in ATG16L1 is associated with improved survival in human colorectal cancer and enhanced production of type I interferon

Abstract: ObjectiveATG16L1 is an autophagy gene known to control host immune responses to viruses and bacteria. Recently, a non-synonymous single-nucleotide polymorphism in ATG16L1 (Thr300Ala), previously identified as a risk factor in Crohn's disease (CD), was associated with more favourable clinical outcomes in thyroid cancer. Mechanisms underlying this observation have not been proposed, nor is it clear whether an association between Thr300Ala and clinical outcomes will be observed in other cancers. We hypothesised t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 52 publications
3
56
0
4
Order By: Relevance
“…This is consistent with the elevated risk of IBD patients to develop colorectal cancer (Ekbom et al, 1990). Human patient data also suggest that bulk autophagy is not perturbed in colorectal cancer cells carrying the ATG16L1 T300A variant, while the level of type I interferon is highly elevated and improves survival (Grimm et al, 2016). These findings support a proposal that the differentiation and proper functioning of Atg16 mutant EE/Paneth cells does not depend on bulk autophagy.…”
Section: Discussionsupporting
confidence: 75%
“…This is consistent with the elevated risk of IBD patients to develop colorectal cancer (Ekbom et al, 1990). Human patient data also suggest that bulk autophagy is not perturbed in colorectal cancer cells carrying the ATG16L1 T300A variant, while the level of type I interferon is highly elevated and improves survival (Grimm et al, 2016). These findings support a proposal that the differentiation and proper functioning of Atg16 mutant EE/Paneth cells does not depend on bulk autophagy.…”
Section: Discussionsupporting
confidence: 75%
“…28 In a recent study, ATG16L1 (T300A) was found to be associated with reduced metastasis in colorectal cancer patients. 36 Collectively, these observations indicate that our finding of an association between SNPs and BM in patients with NSCLC may be biologically plausible.…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, during the preparation of the manuscript, it was reported that the T300A variant of ATG16L1 was associated with strong type I IFN responses and improved survival in patients with CRC (ref. 41). In addition, we found that the morphology of Paneth cells and goblet cells was abnormal in the tumour-free mucosa of Apc +/− Atg7 −/− mice, resulting from the attachment of some bacteria to the epithelium.…”
Section: Discussionmentioning
confidence: 93%